The deafness gene DFNA5 induces programmed cell death through mitochondria and MAPK-related pathways - Van Rossom, Sofie; Op de Beeck, Ken; Hristovska, Vesna; Winderickx, Joris; Van Camp, Guy (Frontiers in Cellular Neuroscience, 2015)
Cell death exists in many different forms. Some are accidental, but most of them have some kind of regulation and are called programmed cell death. Programmed cell death is a very diverse and complex mechanism and must be tightly regulated. This study investigated programmed cell death induced by DFNA5, a gene responsible for autosomal dominant hearing loss and a tumor suppressor gene involved in frequent forms of cancer. Mutations in DFNA5 lead to exon 8 skipping and result in hearing loss (HL) in several families. Expression of mutant DFNA5, a cDNA construct where exon 8 is deleted, was linked to programmed cell death both in human cell lines and in Saccharomyces cerevisiae. To further investigate the cell death mechanism induced by mutant DFNA5, we performed a microarray study in both models. We used wild-type DFNA5, which does not induce cell death, as a reference. Our data showed that the yeast pathways related to mitochondrial ATP-coupled electron transport chain, oxidative phosphorylation and energy metabolism were up-regulated, while in human cell lines, MAP kinase-related activity was up-regulated. Inhibition of this pathway was able to partially attenuate the resulting cell death induced by mutant DFNA5 in human cell lines. In yeast, the association with mitochondria was demonstrated by up-regulation of several cytochrome c oxidase genes involved in the cellular oxidative stress production. Both models show a down-regulation of protein sorting- and folding-related mechanisms suggesting an additional role for the endoplasmic reticulum (ER). The exact relationship between ER and mitochondria in DFNA5-induced cell death remains unknown at this moment, but these results suggest a potential link between the two.